2018
DOI: 10.1002/ajp.22896
|View full text |Cite
|
Sign up to set email alerts
|

The microbial reproductive ecology of white‐faced capuchins (Cebus capucinus)

Abstract: Changes in reproductive status influence energy and nutrient requirements in female primates. The gut microbiota may buffer changes in energy demands, with shifts in community composition increasing the energy production potential of the gut during pregnancy and lactation. In this study, we examine changes in the gut microbiome of wild, female white-faced capuchins (Cebus capucinus) across different reproductive states. Fecal samples (n = 39) were collected from five adult females over the course of a year. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 59 publications
3
40
0
Order By: Relevance
“…The spread of these microbes between members of a social group and corresponding fluctuations in potentially probiotic bacteria such as Bifidobacterium Lactobacillus and in this context warrants further investigation. Finally, the reproductive state of females has been found to have a significant effect on gut microbiota in humans (Koren et al, ) and white‐faced capuchins (Mallott & Amato, ). Because we study adult females, it is possible that variation due to reproductive state is confounding our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of these microbes between members of a social group and corresponding fluctuations in potentially probiotic bacteria such as Bifidobacterium Lactobacillus and in this context warrants further investigation. Finally, the reproductive state of females has been found to have a significant effect on gut microbiota in humans (Koren et al, ) and white‐faced capuchins (Mallott & Amato, ). Because we study adult females, it is possible that variation due to reproductive state is confounding our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, primates whose diet is dominated by ripe fruits or during seasons in which ripe fruits represent their major dietary component are characterized by a microbiome dominated by taxa associated with the processing and fermentation of simple sugars (Amato, ; Gomez et al, ; Hale, Tan, Knight, & Amato, ; Mallott, Amato, Garber, & Malhi, ; Springer et al, ). There also is evidence that host age, sex, group membership, kinship, or reproductive status may influence the alpha diversity and composition of the gut microbiome (Aivelo, Laakkonen, & Jernvall, ; Amato et al, ; Bennett et al, ; Mallott & Amato, ; Schnorr et al, ; Springer et al, ; Tung et al, ), as both sharing of microbes because of proximity or social interactions and individual differences in nutrient needs, diet, genetics, and physiology shape the gut microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been multiple papers published describing changes in the gut microbiota of the Cebus capucinus , commonly referred to as the white‐faced capuchin, due to factors such as diet, seasonality, and reproduction through analysis of fecal samples (Mallott & Amato, ; Mallott, Amato, Garber, & Malhi, ; Orkin et al, ). Findings indicated that the gut microbiota was dominated by taxa from phylums Firmicutes and Proteobacteria (Mallott et al, ).…”
Section: Introductionmentioning
confidence: 99%